Analysis of stress singularity in adhesive joints using meshless methods - Ramalho, L.D.C.; Dionísio, J.M.M.; Sánchez-Arce, I.J.; Campilho, R.D.S.G.; Belinha, J. (Engineering analysis with boundary elements, 2022)
Recent years saw a rise in the application of bonding techniques in the engineering industry. This fact is due to the various advantages of this technique when compared to traditional joining methods, such as riveting or bolting. The growth of bonding methods demands faster and more powerful tools to analyze the behavior of products. For that reason, adhesive joints have been the subject of intensive investigation over the past few years. Recently, a fracture mechanics based approach emerged with great potential to evaluate joint behavior, called Intesity of Singular Stress Fields (ISSF), similar to the Stress Intensity Factor (SIF) concept. However, it allows the study of multi-material corners and does not require an initial crack. This approach was not yet tested with meshless methods. The present work intends to fill this gap, resorting to the Radial Point Interpolation Method (RPIM). With this purpose, adhesive joints with four different overlap lengths (LO) bonded with a brittle adhesive were studied. The interface corner's stresses were also evaluated. The predicted strengths were compared with the experimental data to assess the accuracy of the applied methods. In conclusion, the ISSF criterion proved to be applicable to meshless methods, namely the RPIM.